A reception analysis of Kasambahay on the Kasamabahay Law - Cuñado, Sydney A.
The study generally aimed to get the reception of kasambahay on the Kasambahaw Law since they are considered the primary stakeholder of the law, thus their understanding of the law is significant. Specific objectives of the law were set: (1) determine the communication tools used by SSS, Pag-IBIG and PhilHealth to transfer information to people specifically kasambahay regarding Kasambahay Law; (2) assess the information-transfer of SSS, Pag-IBIG and PhilHealth on the benefits of the kasambahay in each agency using the communication tools produced by the three implementing agencies; (3) to know how kasambahay understand RA10361 or Kasambahay Law in general. The respondents of the study are all identified kasambahay in St. Therese Subdivision, Visayan Village, Tagum City. The locale of the study was chosen through purposive sampling procedure. Three phases were carried out in the study: (1) communication audit; (2) information transfer; and (3) reception analysis. The first phase was done through interview with representatives from the three implementing agencies of the law, (SSS, Pag-IBIG and PhilHealth). On the other hand, survey was applied in the second and third phase of the study. The results in the first phase of the study showed that there are communication tools and efforts that the two of the implementing agencies (SSS & Pag-IBIG) have utilized in informing people regarding Kasambahay Law. Meanwhile, PhilHealth did not conduct any information dissemination efforts since they are still waiting for the action of the regional office as their efforts are synchronized with the regional branch. Moreover, in the second phase of the study it was found that the benefits from the three implementing agencies are very well understood by the respondents. However, there is very low number of the registered kasambahay in the three agencies from the area of the study with PhilHealth-12, SSS-10, and Pag-IBIG-4 kasambahay. It can be seen that even if PhilHealth utilized communication efforts as identified in the first phase of the study, this agency has the highest number of registered kasambahay in St. Therese. This data implies that respondents received the message of PhilHealth from the people around and they considered health benefits from this agency to be given the most priority among all other benefits that SSS (loan) and Pag-IBIG (housing) could provide. Lastly, reception analysis phase showed that kasambahay received the law as beneficial, however, became ineffective since they were not able to experience the benefits stated in the law particularly the registration in the three implementing agencies. The result showed that the diffusion of the new law as analyzed through the Diffussion Innovation Theory by Stuart Hall, was not fully realized since the primary stakeholder of the law who are the kasambahay did not able to experience the positive effect of its implementation. With this, in order to increase not only kasambahay but significantly employers? participation, communication interventions must be done. The communication efforts must target the kasambahay and their employer, specifically highlighting the use of tacit knowledge transfer strategies that include face-to-face (group) that is best suited when the knowledge must be something that many people can benefit from.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Speech/Corporate Communication